Electronic structure of the unoccupied electron energy states in FeSe1−xTex. (October 2015) - Mishra, Pramita; Lohani, Himanshu; Maniraj, M.; Nayak, Jayita; Zargar, R.A.; Awana, V.P.S.; Barman, Sudipta Roy; Sekhar, Biju Raja
Abstract: Inverse photoemission spectroscopic (IPES) measurements along with LDA based band structure calculations have been used to investigate the unoccupied electronic structure of FeSe1− x Te x system. The observed doping and temperature dependent pseudogap in this system is found to be linked to the change in the chalcogen height in their geometric structure. The depletion in spectral weight from the near E F states at low temperature in IPES has been correlated with the enhancement of the 3 z 2 – r 2 orbitals in the photoemission spectroscopy (PES). The Coulomb correlation energy U, estimated from the combined PES and IPES spectra, signifies the enhancement in electron correlations in FeSe1− x Te x, with doping. The formation of pseudogap in PES and IPES confirms the importance of correlations in the 11 family of Fe superconductors. Abstract : Highlights: Doping and temperature dependent pseudogap in FeSe1− x Te x in inverse photoemission spectroscopy. LDA based calculations in support of the experimental results. Depletion in spectral weight at Fermi level is linked to the chalcogen height. The increasing trend of Coulomb correlation energy with Se doping.